MOLECULAR IDENTIFICATION OF A LOCAL LACTIC ACID BACTERIA (LAB) ISOLATE (B21) AND PRIMER CONFIRMATION FOR D-Lactate Dehydrogenase (D-LDH) GENE ISOLATION - Astuti; Madhani, Anisa Tiara; Nurcahyo, Heru; Octavia, Bernadetta; Mercuriani, Ixora Sartika (Universitas Negeri Yogyakarta in collaboration with Perhimpunan Biologi Indonesia, 2023)
This study aims to identify a lactic acid bacteria (BAL) isolated from native chicken (Gallus gallus domesticus) intestinum (B21) based on 16S rRNA gene sequence and also to confirm primers for PCR-based D-Lactate dehydrogenase (D-LDH) gene isolation. The genomic DNA of B21 was isolated then amplified using 16S rRNA. The PCR product then sequenced and aligned. The sequencing was done in 1st Base Pte. Malaysia. The sequence then aligned using the Basic Local Alignment Search Tool (BLAST) in NCBI to know the similar genome species. Isolation D-LDH gene was done through PCR using 5 primers (idb 0101, idb 1147, idb 0813, idb 1010, and idb 2021) of B21 and also J15 isolate genome. The PCR product were then sequenced and aligned with the D-LDH gene sequences in NCBI. The results of molecular identification based on 16S rRNA markers showed that B21 has 99.45% similarity to Bacillus proteolyticus. Amplification of the LDH gene with idb 1010 primer on J15 isolate yielded 4 fragments (i.e. 650, 1400, 1500, and 1700bp). The results of phylogenetic tests showed that the 1700bp fragment has a high similarity to the D-LDH gene in Myobacterium tuberculosis species with a bootstrap value of 84%. While other size fragments cannot be trusted to have similarity to LDH sequence because they have not reached the minimum bootstrap value that meets the qualifications.